The Mapping the Current Practice of Religious Character Education Management Based on Islamic Religious Education: A Multi-Case Study in Islamic Elementary Schools in Balikpapan City, Indonesia - Suriansyah Suriansyah; Nur Hasanah (Global Education Journal, 2026)
Religious character education based on Islamic Religious Education (IRE) plays an important role in strengthening students' moral and spiritual development. However, evidence regarding its management in Islamic elementary schools remains limited. This study aims to describe the management of IRE-based religious character education in three Islamic elementary schools in Balikpapan City, Indonesia, through five management functions: planning, organizing, actuating, controlling, and innovation. A descriptive qualitative multi-case study was conducted as the preliminary needs analysis stage of a broader research and development project. Data were collected through interviews, participant observation, focus group discussions, and document analysis involving principals, IRE teachers, and parents. Data were analyzed using the Miles and Huberman interactive model with credibility, transferability, dependability, and confirmability procedures. The findings indicate that religious habituation programs, including congregational prayer, Qur'an memorization, and character-building activities, have been implemented in all schools. However, these programs are managed as routine activities rather than as an integrated management system. Planning remains normative without systematic needs assessment, organizing depends largely on IRE teachers, controlling lacks standardized evaluation instruments, and innovation is limited and unsustained. Cross-case analysis also reveals weak collaboration between schools and families in reinforcing religious character, especially during school holidays. The study concludes that an integrated, evidence-based management model is needed to improve the effectiveness and sustainability of religious character education in Islamic elementary schools.